Tidens rytmik - Stougaard-Nielsen, Jakob (K&K - Kultur og Klasse, 2006)
Dante Alighieri, William Carlos Williams’ prosodi og Michel Serres Rhythm of Time The article discusses William Carlos Williams’s poetics and his particular conception of a modern prosody as expressed in the essay »Speech Rhythm« (1913) and as materialized in his experiments with a poetic form he himself termed »the variable foot« in »the triadic verse«. The article suggests that Williams’s poetics should be conceived as both an attempt to reinvigorate a typographically governed poetic language, his reaction to free verse, and as a larger figure for a poetic project which attempts to offer a poetic form to an unruly American idiom. Additionally, Williams’s new poetic measure is considered as an attempt to produce a poetic voice that could capture the rhythms and temporalities suggested by the modern age. Williams’s poetics present, then, a conflation of poetic scheme and trope, of prosody and anthropology, and are presented here as in tune with Ezra Pound, George Antheil, Albert Einstein and Michel Serres’ aesthetic and scientific abstractions of temporality. Williams’s poetic experiments offer a new measure for a modern »time«.